Lifetime prediction and analysis of AlGaN/GaN HEMT devices under temperature stress. (March 2022) - Wang, Baozhu; Zhao, Jinyuan; Zhang, Ming; Yang, Lin; Wang, Jianchao; Hou, Weimin
Abstract: AlGaN/GaN HEMT (High Electron Mobility Transistor) devices are widely used in power electronic equipment due to their excellent properties such as low on-resistance and high breakdown voltage. Power electronic equipment usually faces high frequency, high temperature and other extreme environments when they are in use. Excessive environmental stress will accelerate the aging of devices. When the aging reaches a certain level, it will cause devices to fail, and even cause the entire circuit to fail. Therefore, the lifetime of AlGaN/GaN HEMT devices has always been a research hotspot. Based on the three temperature DC tests results of GaN HEMT devices with different gate widths, the lifetime of GaN HEMT devices at normal operating temperature is predicted by using multiple linear regression method and graph estimation method. The channel temperature of devices is 150 °C. The prediction results show that when GaN HEMT devices are in normal use, the median lifetime is greater than 10 7  h. The lifetime of the 1.25 mm gate width devices is significantly longer than that of the 3.6 mm gate width devices. It can be inferred that the smaller the gate width of devices, the longer the service lifetime. The acceleration factor of 3.6 mm gate width devices is 5.9 × 10 4, the acceleration factor of 1.25 mm gate width devices is 2 × 10 4 . The larger the gate width of the device, the larger the acceleration factor and the easier the device will fail. Highlights: By the lifetime prediction, it is found that the median life of GaN HEMT devices is longer than 10 7  h at normal operating temperature. By comparative analysis, the gate width of devices has some influence on its service life. The smaller the gate width, the longer the lifetime of AlGaN/GaN HEMT devices.